The Block Statue of Djedhor son of Tjanefer (Cairo JE 37200) - Rashed, Mohamed Gamal.
The article represents the first publication of a block statue of the Theban priest Djedhor son of Tjanefer dated sometime between the late Thirtieth Dynasty to the early Ptolemaic period. The statue, from the Karnak Cachette, is now in the Egyptian Museum in Cairo (JE 37200). It follows a style that is common to block statues of this period. Its hieroglyphic inscriptions are rich with paleographical characteristics of the period. The inscriptions include the regular formulae to the gods of Karnak whom the owner’s family served for decades. In addition to the titles of the owner, it provides information about his family’s priestly ranks. Though its inscriptions do not give enough information to prove his genealogy with certainty, a suggested genealogical tree up to the fourth generation of his family has been drawn with possible links to other monuments of a well-known family of this period. http://dx.doi.org/10.5913/jarce.55.2019.a008